Intimasi Seksual dalam Menjaga Keharmonisan Rumah Tangga - Matondang, Fatiha Sabila Putri; Putri, Alvina Dwi Juliantika; Nasution, Fadilah Wisdaniah; Hadi, Muhammad Ilham; Lingga, Taufiq Maulana (Medan Resource Center, 2024)
Family harmony is the goal of every marriage and can be achieved through the mutual efforts of the husband and wife to love each other and develop spiritual behavior in their family life. This study aims to analyze the role of spirituality as a moderating variable that can strengthen the relationship between love and family harmony. The research employs quantitative methods, utilizing surveys and statistical analysis to measure the impact of spirituality on the love-harmony dynamic. Results indicate that cultivating feelings of love in married couples significantly enhances family harmony. Furthermore, the integration of spirituality in daily life serves to reinforce this relationship, suggesting that spiritual practices and beliefs play a crucial role in fostering a harmonious family environment. This study concludes that love and spirituality are interlinked elements essential for achieving and maintaining family harmony.